1998
DOI: 10.1021/ie970543q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Hydrolytic Depolymerization of Melt Poly(ethylene terephthalate)

Abstract: The hydrolytic depolymerization of poly(ethylene terephthalate) (PET) was carried out in a stirred batch reactor at 235, 250, and 265 °C above its melting point and under autogenous pressure. The solid products which were mainly composed of terephthalic acid were analyzed by potentiometric titration and elemental analysis. The liquid products which were mainly composed of ethylene glycol and a small amount of its dimer were analyzed by gas chromatrography. A kinetic model consisting of forward and backward rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 10 publications
4
76
0
4
Order By: Relevance
“…In a study in our lab on the hydrolysis of PET with water in the absence of alkaline hydroxides under pressure to keep water in the liquid state, the hydrolysis did not significantly occur until about 235°C. 19 Therefore, water should not directly participate in the alkaline hydrolysis at lower temperatures. It is noted that the peak shape of ethylene glycol for the hydrated and dry samples (Fig.…”
Section: Hydration Effect On Alkaline Hydrolysis Of Pet With Potassiumentioning
confidence: 99%
“…In a study in our lab on the hydrolysis of PET with water in the absence of alkaline hydroxides under pressure to keep water in the liquid state, the hydrolysis did not significantly occur until about 235°C. 19 Therefore, water should not directly participate in the alkaline hydrolysis at lower temperatures. It is noted that the peak shape of ethylene glycol for the hydrated and dry samples (Fig.…”
Section: Hydration Effect On Alkaline Hydrolysis Of Pet With Potassiumentioning
confidence: 99%
“…• b -uso de altas temperaturas [8][9][10] ; e • c -altas pressões [10,11] . Em trabalhos recentes Ruvolo Filho e colaboradores estudaram a despolimerização do PET [12][13][14][15] e mostraram usando soluções de NaOH em etilenoglicol 1,1 mol.L -1 [12] que a cinética de despolimerização abaixo da temperatura de fusão do PET é um processo heterogêneo que ocorre na superfície do PET e depende da velocidade de agitação em que é realizada a reação.…”
Section: Methodsunclassified
“…Researchers [12] have studied polyester hydrolysis using catalyst and reported that the corresponding reaction rate constants were found to be about 20% greater than those obtained for uncatalyzed hydrolysis. However, later, other researchers [13] have reported that polyester hydrolysis in excess water was found to be an auto-catalyzed process and their rates were significantly greater than those obtained by researchers [11,12] , who showed different predictions for polyester hydrolysis using excess water at higher temperatures. Furthermore, separation of solids from the liquid phase was not clearly mentioned, and recovery of liquid monomeric product from the aqueous phase was not reported by researchers [11][12][13] .…”
mentioning
confidence: 86%
“…However, later, other researchers [13] have reported that polyester hydrolysis in excess water was found to be an auto-catalyzed process and their rates were significantly greater than those obtained by researchers [11,12] , who showed different predictions for polyester hydrolysis using excess water at higher temperatures. Furthermore, separation of solids from the liquid phase was not clearly mentioned, and recovery of liquid monomeric product from the aqueous phase was not reported by researchers [11][12][13] . The solids were washed [11][12][13] with water that would not remove the complete deposition from the surface.…”
mentioning
confidence: 86%